De collectie Roef-Meelker en public : een schenking aan de gemeente Helmond. - Hoenjet, Frank (Helmond : Gemeentemuseum Helmond, 2001)
Alechinsky, Pierre ; Appel, Karel ; Atlan, Jean M ; Bissière, Roger ; Brands, Eugène ; Chadwick, Lynn ; Constant ; Corneille ; Gillet, Roger ; Gregoor, Jan ; Gijsen, Jo ; Heerup, Henry ; Hepworth, Barbara ; Jorn, Asger ; Kuijpers, Theo ; Lanskoy, André ; Lataster, Ger ; Manessier, Alfred ; Marcoussis, Louis ; Masson, André ; Nanninga, Jaap ; Ouborg, Piet ; Pignon, Edouard ; Riopelle, Jean Paul ; Snijders, Ad ; de Staël, Nicolas ; van Velde, Bram ; van Velde, Geer ; Visser, Carel ; Volten, Andre ; Wagemaker, Jaap ; Wolvecamp, Theo
boek